HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KOMITMEN ORGANISASI PADA KARYAWAN HOTEL - Wendy Wendy Souisa (Movere Journal, 2022)
This study aims to determine the relationship between emotional intelligence and organizational commitment to hotel employees in Ambon City. The sample for this study was several different hotel employees in Ambon City totaling 60 people. This study uses a correlation test to determine the level of closeness of the relationship between emotional intelligence variables and organizational commitment, where organizational commitment is divided into three parts, namely affective commitment, continuance commitment, normative commitment. This study found that emotional intelligence had a significant effect on affective commitment and continuance commitment, and emotional intelligence had no significant effect on normative commitment. From this study, the researcher recommends that the factor of emotional intelligence be included in the selection and recruitment standards for hotel employees in Ambon City at all levels